Merdeka Belajar-Kampus Merdeka (MBKM) Curriculum in English Studies Program: Challenges and Opportunities - Kriswanda Krishnapatria (ENGLISH EDUCATION DEPARTMENT - UNIVERSITAS SINGAPERBANGSA KARAWANG, 2021)
Abstract This article was written with the impetus to see the implementation of the Merdeka Belajar (Freedom to Learn), Kampus Merdeka (Independent Campus) program launched by the Ministry of Education and Culture (Indonesia), particularly on the policy of students’ right to take up to three semesters outside of their program. This policy aims to give students independence in developing their own knowledge and interests so that they will be better prepared upon graduation. In practice, the application of this curriculum innovation is not as smooth as expected because the study program faces various challenges, both technical and administrative, when facilitating students in pursuing their studies. To date, many researchers have reviewed Merdeka Belajar, Kampus Merdeka (MBKM) policies in Higher Education, but there has been yet article specifically discussing the implementation of students’ rights from English Studies program in taking credits outside their study program, so this research attempts to fill this gap. In this qualitative descriptive study, the method used was observation and documentation. Data were collected from learning activities at the English Studies Program, Faculty of Cultural Sciences, Universitas Padjadjaran, in the 2020/2021 Academic Year. The results of the study show that the main challenge in implementing MBKM curriculum and its policy is administrative issues such as building partnership between study programs and external parties. However, one of the positive aspects of the COVID-19 pandemic is that the online learning turns out to be very supportive for the implementation of this program. It is more likely that the program stays open for opportunities and there is room for improvement by offering more elective courses in the curriculum to give students more freedom.